The Implementation of Rewards and Punishments in Fostering Student Discipline at Pondok Pesantren Modern Islam Assalaam Sukoharjo - Tin Tisnawati; Meti Fatimah (Didaktika: Jurnal Kependidikan, 2024)
This study aims to explore how rewards and punishments are applied to foster student discipline at Pondok Pesantren Modern Islam Assalaam Sukoharjo. This is a qualitative descriptive study. The subjects of the research are students and dormitory supervisors at Pondok Pesantren Modern Islam Assalaam Sukoharjo. The study was conducted from July to September, with research informants including the head of student affairs, dormitory supervisors, administrators, and students. Data were collected through observation, structured interviews, documentation, and relevant literature. Data analysis was divided into several stages: data collection, data reduction, data display, and conclusion drawing. The findings show that the implementation of rewards and punishments effectively fosters student discipline at Pondok Pesantren Modern Islam Assalaam Sukoharjo. Rewards include praise, recognition, certificates, and gifts, while punishments include verbal warnings, social punishment, material punishment, physical punishment, and administrative actions. This system has proven to enhance student motivation, discipline, and achievements, creating a conducive environment for spiritual, intellectual, and moral development.